Religion after deliberative democracy - Stanley, Timothy (Routledge studies in religion and politics, 2022)
"Religion after Deliberative Democracy responds to gaps exposed by the case of religion in deliberative democratic theory. Religion's persistent visibility in political life has called for new solutions for healing deeply divided societies. In response, the author begins with Jeffrey Stout's pragmatist vision of democracy before providing a series of supplements in subsequent chapters. Past legacies are refigured in a rapprochement with Jürgen Habermas's work which is differentiated from the distinctive relevance of Hannah Arendt's Vita Activa. New developments in comparative political theology are complemented by recent systems theory approaches to institutional interactions. Peaceful protest movements are reframed in light of the trust-building capacities of minipublics. The result is reason for renewed confidence in democratic practices attuned to fostering political plurality and capable of responding to persistent religious partisanship. This book fills a crucial space in the literature on religion and democracy and will be of interest to students and scholars of philosophy of religion, theology, pragmatism, and political theory"--